Analysis of the Theory of Legislation in the Constitutional Review Procedure of the Democratic Republic of Timor-Leste in 2002 - Trindade, Engracia; da Silva, Avelino M. Coelho; Araújo, Julio da S. (Sahabat Publikasi, 2025)
This research addresses the challenges of the 2002 RDTL Constitution in the Democratic Republic of Timor-Leste, focusing on its rigidity and outdated provisions that no longer align with contemporary societal needs. The study explores the theoretical, juridical, and sociological issues surrounding the constitution, highlighting the need for constitutional amendments. The research methodology employed is normative, utilizing legislative, conceptual, and comparative approaches. The study identifies issues such as disharmony in norms due to outdated articles, conflicts between different constitutional clauses, and the implications of an unamended constitution on state administration and the protection of citizens' constitutional rights. The paper suggests that the national parliament, in collaboration with the President and government, should prioritize constitutional amendments to ensure the legal framework addresses current challenges, including technological advances and changing societal conditions. The research underscores the importance of constitutional flexibility to maintain a stable and responsive legal order